Georgia’s Experience in the Context of the Development of Human Trafficking: Historical, Social, and Legal Analysis - Kvaracxelia, Giorgi (European Scientific Journal, ESJ, 2026)
The article presents an integrated analysis of the historical evolution and contemporary trends of human trafficking in the context of international and national experience. The aim of the study is to comprehensively assess the genesis of trafficking, its transnational nature, socio-economic determinants, and the dynamics of the development of legal regulation in order to form an effective preventive policy in the Georgian context. The work is based on doctrinal-legal, comparative-legal, and historical-critical analysis. The main instruments of international law are studied, including the International Agreement for the Suppression of the White Slave Traffic and the Palermo Protocol, as well as the normative framework developed within the United Nations. An assessment of the degree of harmonization of international standards and Georgian national legislation is carried out. The study also includes an interdisciplinary analysis that combines criminological, sociological, and economic perspectives in order to identify the structural transformation of trafficking and its modern forms—labor, sexual, and organ exploitation. The analysis shows that trafficking is a historically transformed phenomenon, which, under the conditions of globalization, has taken the form of organized and transnational crime. Special attention is paid to the post-Soviet space, where the economic crises following the collapse of the Soviet system, institutional weakness, and social destabilization have become important factors in the expansion of the phenomenon. The paper critically analyzes the relationship between prostitution and trafficking, emphasizing the impact of technological progress and digital platforms on the increase in the latency of crime, as well as the role of economic inequality in the process of involving vulnerable groups in exploitation. The study concluded that effective prevention of human trafficking requires a complex and multi-sectoral approach that combines legal, social, economic, and educational policies. Particular importance is attached to the harmonization of national legislation with international standards, the strengthening of specialized institutional mechanisms, an effective system of protection and reintegration of victims, as well as the deepening of regional and international cooperation. The work creates a theoretical and practical basis for the development and implementation of a modern, evidence-based policy against trafficking in Georgia.